Prevalence of anaemia among children under five years in tertiary care hospital of Nepal. - Joshi, Sundari; Pradhan, Megha Pradhan; Joshi, Ujjwal (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Anaemia is a pathologic deficiency in oxygen-carrying haemoglobin in red blood cells which may be the result of genetic diseases, infections and deficiency of several nutrients. Nepal is one of the developing countries where anaemia is one of the most serious public health problems. So, a study was planned to evaluate the prevalence of anaemia among children under five years in tertiary care hospital of Nepal. Methods: A cross-sectional study was carried out from August 2011 to January 2012 using a structured questionnaire interview and observation. The children were divided into three groups: group I (0-1 years), group II (>1-3 years), group III (>3-5 years). Anaemia was assessed using haemoglobin measurement in gram in decilitre on Sysmex KX -21 (automated haematology analyzer). The severity of anaemia were grouped as follows: severe anaemia, < 7.0 g/dL; moderate anaemia, 7.0 to 8.9 g/dL; and mild anaemia, 9.0 to 10.9 g/dL as per WHO classification. Stool test was also carried out to assess worm infestation. Data were analysed using SPSS 11.5. Results: There were 208 children among which 52.9 % were male while 47.10 % were female. The overall prevalence of anaemia was found to be 49.5% of which 43.3% had mild, 15.8% had moderate and 0.5% had severe anaemia. Out of 20 children in group I, 70 % were anaemic. Among the 94 each in group II and group III, children suffering from anaemia were 51% and 43% respectively. The stool investigations showed that 5.3 % children suffered from worm infestations. Conclusions: prevalence of anaemia was seen in 49.5% of children below five years age group and the diet and worm infestations didn’t affect it. doi: http://dx.doi.org/10.3126/mjsbh.v13i1.12998